NILAI TRADISI LISAN ODHONG-ODHONG SEBAGAI FONDASI HARMONI SOSIAL MASYARAKAT PAKPAK BHARAT: KAJIAN LITERATUR - Arlin Septia Basana Siagian; Rahma Hidayati; Dia Ananda Putri; Poppy Amalia; Tri Indah Prasasti (STKIP Subang, 2026)
The odhong-odhong oral tradition is a distinctive chant of the Pakpak Bharat community that embodies essential life values as the foundation of social harmony. This study aims to describe the nature and characteristics of odhong-odhong, identify the values contained within it, analyze the role of those values in building social harmony, and examine its relevance in the era of modernization and globalization. This study employs a descriptive qualitative method through a literature review approach, drawing on scientific journals, books, and relevant literature published within the last six years. The findings reveal that odhong-odhong is a chant performed by Pakpak men while searching for frankincense resin in the forest, functioning simultaneously as emotional expression, prayer, and a medium for transmitting cultural values. The values embedded in this tradition include emotional, moral, social, spiritual, and cultural dimensions. From the perspective of Émile Durkheim's solidarity theory, odhong-odhong strengthens the mechanical solidarity of the Pakpak Bharat community through collective consciousness formed by shared values and communal experiences. Despite facing the threats of modernization, including declining interest among younger generations and limited documentation, odhong-odhong remains relevant as a cultural identity that must be preserved through educational integration, digitalization, and revitalization in traditional ceremonies.